RURALITES SOURCES OF INFORMATION ABOUT CHANGES IN SOUTH-WESTERN NIGERIA - AKINBODE, I. ADEFOLU (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
This paper examines the sources of information used by the rural inhabitants of South-western Nigeria to learn about the different changes introduced by the military regimes. The underlying assumption is that the different types of information sources available to the rural population have varying effectiveness in communicating different changes. The data used were gathered from secondary sources as well as from randomly selected four hundred household heads using interview schedules. Our analyses reveal that: